Functional anatomy reveals secretory activity in papillose anthers of a buzz‐pollinated Solanum species (Cyphomandra clade – Solanaceae). (17th April 2018) - Falcão, B. F.; Stehmann, J. R.
Abstract: Pollination in Solanum (Solanaceae) species is commonly performed by female bees, which vibrate anthers to extract pollen. Another pollen removal type is by male euglossine bees, milking the anthers when searching for floral scents produced by secretory tissues (osmophorous) at the swollen connective of the anthers of species in the Cyphomandra clade. Some species of this clade, however, are buzz‐pollinated and present papillate anthers that should also have secretory activity, a hypothesis here tested. The anthers of Solanum luridifuscescens were fixed at different stages of development and analysed under light microscopy, SEM and TEM. Histochemical tests for the detection of starch and lipids were done. Epidermal cells of the abaxial surface of the anthers were visibly papillose, had large nuclei and dense cytoplasm rich in organelles such as mitochondria and plastids, typical features of secretory tissues. In this site, lipid droplets were detected, concomitantly with starch consumption, compatible with the secretory process in osmophores. No exudate or accumulation of substances was seen on the surface; in agreement with a previous pollination study performed in field conditions, where no pollinators were observed collecting floral scents, only pollen. The histochemical and structural analyses have evidenced the lipidic composition of the secretion, strongly pointing to terpenes as the secreted compounds. Ours findings show that papillae of the anthers have secretory activities that produce lipophilic compounds. This does not result in resources for bees, but could be an evolutionary step to the development of more specialised anthers in the Cyphomandra clade.